Republic of South Sudan : First Review under the Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
A 9-month Staff Monitored Program (SMP) combined with a disbursement under the Rapid Credit Facility (RCF) of 50 percent of quota (about USD 174 million) was approved on March 30, 2021 to address BOP challenges and build a track record towards an upper credit tranche financial arrangement. This followed a disbursement under the RCF in November 2020 of 15 percent of quota (about USD 52 million), which was the first-ever financial disbursement from the Fund to South Sudan. Progress has continued in implementing the revitalized peace agreement of 2018: following the formation of a unity government in February 2020 and the appointment of state governors in June 2020, the national parliament was sworn into office in August 2021. The humanitarian situation remains dire, with about 60 percent of the population facing high levels of acute food insecurity.